Implementasi Aplikasi E-Surat Pada Badan Kesatuan Bangsa dan Politik Kota Surabaya - Rizki, Alifian Kusuma (Innovative: Journal Of Social Science Research, 2025)
Digital transformation in the public sector has become a critical need to improve efficiency and effectiveness, particularly in the management of administrative correspondence. This study aims to analyze the implementation of the e-Surat application at the Badan Kesatuan Bangsa dan Politik (Bakesbangpol) of Surabaya City as a digital solution for managing incoming and outgoing letters. The research method used is a descriptive qualitative approach, with data collection techniques including semi-structured interviews, direct observations, and documentation. The results of the study indicate that the implementation of the e-Surat application at Bakesbangpol has successfully improved administrative management efficiency, particularly in recording, distribution, and archiving letters. Compared to the manual system, the application reduces the processing time of incoming correspondence by up to 40% and minimizes the risk of document loss by 85%. Furthermore, the e-Surat application promotes transparency and accountability through integrated document tracking features. However, some challenges persist, such as limited digital competencies among staff and technical issues, including network instability. This study concludes that the e-Surat application is an effective innovation in supporting the digitalization of government administration, with the potential for adoption by other agencies. Recommendations include intensive training for staff, strengthening technological infrastructure, and periodic evaluations of the e-Surat system to ensure its sustainability.